A practical high-energy cathode for sodium-ion batteries based on uniform P2-Na0.7 CoO2 microspheres - Fang, Yongjin (2020)
Layered metal oxides have attracted increasing attention as cathode materials for sodium-ion batteries (SIBs). However, the application of such cathode materials is still hindered by their poor rate capability and cycling stability. Here, a facile self-templated strategy is developed to synthesize uniform P2-Na0.7 CoO2 microspheres. Due to the unique microsphere structure, the contact area of the active material with electrolyte is minimized. As expected, the P2-Na0.7 CoO2 microspheres exhibit enhanced electrochemical performance for sodium storage in terms of high reversible capacity (125 mAh g-1 at 5 mA g-1 ), superior rate capability and long cycle life (86 % capacity retention over 300 cycles). Importantly, the synthesis method can be easily extended to synthesize other layered metal oxide (P2-Na0.7 MnO2 and O3-NaFeO2 ) microspheres.